The Process of Curriculum Innovation: Dimensions, Models, Stages, and Affecting Factors - Yuli Supriani; Fitri Meliani; Asep Supriyadi; Supiana Supiana; Qiqi Yuliati Zaqiah (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This article aims to explain the dimensions, models, stages, and affecting factors in the curriculum innovation process. Curriculum becomes very important in educational institutions because the curriculum is the